Kitāb al-Tuḥfah al-Rāgibīn wa al-Radd ‘alā ‘Aqīdah al-Wujūdīyah bi Fālimbānj fi al-Qarn al-Thāmin ‘Ashar al-Mīlādī - Nyimas Umi Kalsum (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
This article tries to discuss one of religion waorks written by al-Palimbani, Tuhfah al-Ragibin, presented the discussion of the author's response towards wujudiyyah, a text that widely spread in Palembang at the time. In line with al-Raniri in Aceh, al-Palimbani divided wujudiyyah's doctrine into two categories: wujudiyyah mulhid and wujudiyyah muwahhid.DOI: 10.15408/sdi.v11i3.597